Microplastic Identification in Fisheries Commodities in Sayung Waters, Demak - Fuad Muhammad; H. Hadiyanto; Abdurrafi Alwan (Journal of Bioresources and Environmental Sciences, 2022)
Each year plastic production worldwide has increased. Approximately 10% of the production of plastic will lead to the sea. This plastic is degraded to be a small particle size < 5mm called microplastic. The river is the main route of entry of plastic from land to the sea. Sayung River is a river that has the potential to be contaminated with microplastics around which it is used as a location for the cultivation of various fisheries commodities including Pernaviridis, Penaeus monodon, and Lates calcarifer. The study aims to determine the number and type of microplastic in Penaeus monodon, Pernaviridis, and Lates calcarifer. Samples were taken from three different stations in the coverage area. Microplastic abundance analysis by isolating microplastic on each sample. Isolation samples of Pernaviridis, Penaeus monodon, and Lates calcarifer are done by dissolving the sample in a solution of 10% KOH was allowed for 24 hours at a temperature of 60 oC and observed under a binocular microscope. Founded types of microplastic are fiber, fragments, pellets, and films on Pernaviridis, Penaeus monodon, and Lates calcarifer. Pernaviridis found on many types of films, in Penaeusmonodon are the most prevalent types of fragments and the Lates calcarifer most common types of fiber. Pellet type is the least kind found in Pernaviridis and Penaeus monodon. Based on the age when taken, Penaeus monodon is the commodity that has the most potential to be contaminated with microplastic while based on the number of particles found in Lates calcarifer is the commodity with the most potential to be contaminated with microplastic.